Performance of listed penny stocks in Bursa Malaysia / Noraishah Ismail - Ismail, Noraishah (2017)
This paper was aimed to study the performance of listed penny stocks in Kuala Lumpur Stock Exchange (KLSE) by using several independent variables. This final year project is a compulsory for last semester degree students and become a part of course requirements in order to complete BBA (Hons) Investment Management. This paper roughly wants to determine the relevant factors that influence the performance of penny stocks in Bursa Malaysia. The factors discussed in this research paper are liquidity factor, size of firm's market capitalization factor, risk factor and profitability factor. The performance was measures by using sample period five years from 2010 until 2015 with sample listed penny stocks categorized into two categories which are includes 50 sample stocks priced MYR 1.00 and below. In order to answer the research questions, current ratio, market cap, beta, return on equity and total return were used to represent each factors in this study. The result was derived from the sample of study through Eviews and involved multiple regression model analysis in order to show the relationship between the current ratio, market cap, beta, return on equity and total return towards the performance of listed penny stocks. This study also intended to make a better understanding of penny stocks trading behavior in Malaysia. Either the result that derived from past researcher has any similarities with this study. Furthermore, this paper will try to improve perceptive of penny stocks in Malaysia equity market. Hopefully, this study will gives readers understanding and overview by looking at the performance of penny stocks in Malaysia. On the other hand, may this paper shed some light towards the 'oblivious' penny stocks trading and investigation.